Advances in Stem Cell Therapies for Rotator Cuff Injuries - Wang, Hao-Nan; Rong, Xiao; Yang, Lu-Ming; Hua, Wei-Zhong; Ni, Guo-Xin (Frontiers in Bioengineering and Biotechnology, 2022)
Rotator cuff injury is a common upper extremity musculoskeletal disease that may lead to persistent pain and functional impairment. Despite the clinical outcomes of the surgical procedures being satisfactory, the repair of rotator cuff remain some problems, such as through failure of healing, adhesion formation, and fatty infiltration. Stem cells have high proliferation, strong paracrine action, and multiple differentiation potential, which promote tendon remodeling and fibrocartilage formation and increase biomechanical strength. Additionally, stem cell–derived extracellular vesicles (EVs) can increase collagen synthesis and inhibit inflammation and adhesion formation by carrying regulatory proteins and microRNAs. Therefore, stem cell–based therapy is a promising therapeutic strategy that has great potential for rotator cuff healing. In this review, we summarize the advances of stem cells and stem cell–derived EVs in rotator cuff repair, highlight the underlying mechanism of stem cells and stem cell–derived EVs, and biomaterial delivery systems. Future studies need to explore stem cell therapy in combination with cellular factors, gene therapy, and novel biomaterial delivery systems.